Wpływ siarczanu glinu na wybrane właściwości gleby oraz na wydajność i jakość sadzonek sosny zwyczajnej w leśnej szkółce gruntowej - Januszek, Kazimierz; Błońska, Ewa; Gdula, Anna; Kozieł, Krzysztof; Molicka, Joanna; Stępniewska, Hanna; Wójs, Anna (Leśne Prace Badawcze, 2014)
The alkalization of soil is a common phenomenon in forest ground nurseries. Liming, inadequate fertilization and the use of hard water for irrigation are the main reasons for this alkalization. The aim of this study was to investigate the effect of fertilization with aluminium sulphate on soil pH, the activity of selected soil enzymes, efficiency as well as the growth parameters of pine seedlings. The study was conducted in a forest nursery, on a plot with soil pH 6.4 in water and 5.9 in 1 M KCl. Such a pH is not conducive to the production of conifer seedlings, particularly pines. Two different doses of aluminium sulphate fertilizer were applied: 740 kg ha -1 and 1110 kg ha -1 . Both doses significantly reduced the soil pH, whereas soil enzyme activity did not change. The lower dose had a positive impact on the growth parameters of pine seedlings, while the higher dose led to their deterioration. We observed statistically significant differences in average primary and lateral root lengths, number of short roots, and thickness of the neck root of seedlings. One- and 2-year-old seedlings did not show symptoms of nutrient deficiency and neither did concentrations of the investigated macronutrients and selected micronutrients in needles indicate such. After applying the higher fertilizer dose, we observed a favourable change in the composition of mycorrhizae . Out of the potential seedling pathogens we found Cylindrocarpon spp., Fusarium spp., Phytophthora spp., Pythium spp. and Rhizoctonia solani of which the most frequent were Fusarium oxysporum , Pythium spp. and R. solani. Their occurrence frequency differed between the treatments used in this experiment. This study confirms the positive effects of a low aluminium dose on the performance and growth parameters of pine seedlings. However, on the basis of the conducted experiments, it is difficult to say, whether this positive effect is due to a direct action of aluminium on the seedlings or rather an indirect effect caused by lowering the soil pH, which in turn impacts on mycorrhizae composition and hence pathogen development.